2015
DOI: 10.1098/rsbl.2015.0711
|View full text |Cite
|
Sign up to set email alerts
|

Grooming-at-a-distance by exchanging calls in non-human primates

Abstract: The 'social bonding hypothesis' predicts that, in large social groups, functions of gestural grooming should be partially transferred to vocal interactions. Hence, vocal exchanges would have evolved in primates to play the role of grooming-at-a-distance in order to facilitate the maintenance of social cohesion. However, there are few empirical studies testing this hypothesis. To address this point, we compared the rate of contact call exchanges between females in two captive groups of Japanese macaques as a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 29 publications
2
53
0
Order By: Relevance
“…interlocutor selectivity) rules, and the frequency of these vocal exchanges was only influenced by social bonds (established by the frequency of occurrence of peaceful spatial proximities). Interestingly, the frequencies of Japanese macaques'( Macaca fuscata ) vocal exchanges were positively correlated with their social bonds (established by grooming duration) (Arlet et al ., ), thus supporting the hypothesis that vocal exchanges can be interpreted as a form of ‘grooming‐at‐a‐distance’ that facilitates the maintenance of social cohesion (Dunbar, ).…”
Section: Theories Of the Origins Of Languagesupporting
confidence: 62%
See 2 more Smart Citations
“…interlocutor selectivity) rules, and the frequency of these vocal exchanges was only influenced by social bonds (established by the frequency of occurrence of peaceful spatial proximities). Interestingly, the frequencies of Japanese macaques'( Macaca fuscata ) vocal exchanges were positively correlated with their social bonds (established by grooming duration) (Arlet et al ., ), thus supporting the hypothesis that vocal exchanges can be interpreted as a form of ‘grooming‐at‐a‐distance’ that facilitates the maintenance of social cohesion (Dunbar, ).…”
Section: Theories Of the Origins Of Languagesupporting
confidence: 62%
“…Based on the literature and our findings (e.g. Arlet et al ., ; Lemasson et al ., ; Prieur et al ., ; Crockford, Wittig & Zuberbühler, ; Fröhlich et al ., ; Hobaiter, Byrne & Zuberbühler, ; Fedurek et al ., ), we propose the multicausal theory of language origins, postulating that primate communicative signalling stems from a cost–benefit trade‐off of signal production and processing of interactants in relation to four interrelated (evolutionary and life cycle) factors, namely species, individual and context‐related characteristics as well as behaviour and its characteristics. The perennial debate concerning the origins of language is presented below.…”
Section: Theories Of the Origins Of Languagementioning
confidence: 98%
See 1 more Smart Citation
“…These calls can facilitate friendly social interactions or act as reconciliatory signals following aggression [49]. In some cases, call exchanges appear to function as long-distance ‘social grooming’, and to reinforce existing social relationships [1011]. …”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have suggested that the exchange of contact calls may function to reinforce individuals’ social bonds, especially when they occur between widely separated partners [1011]. However, it is also possible that these calls are used to monitor the location of important social partners, not to reinforce their bonds.…”
Section: Introductionmentioning
confidence: 99%